ANIMAL MONITORING SYSTEM - (PET SENSOR): an approach involving IoT techniques - Bruno, Diego Renan; Bruno, Lara Alicia Soligo Dardani; Osório , Fernando Santos; Teixeira, Márcio Andrey (Revista Interface Tecnológica, 2022)
In the current world scenario, society is increasingly concerned about the well-being of its domestic animals, especially in terms of health and safety, preventing these animals from having access to the street, thus making it possible to avoid contagion by diseases, accidents and disappearance. . The present work aims to develop an IoT (Internet of Things) system that makes it possible to locate animals that are lost or for adoption, whose ultimate objective is to help tutors or breeders locate their animals through a system of Intelligent Sensors. based on RFID (Radio Frequency Identification) and GPS (Global Positioning System), easy to use and that can be attached to the collar. The sensing system must be applied in conjunction with the use of a cell phone application, created exclusively for the monitoring of animals. Another focus of the work is to manage adoptions through the current location of the animal and its possible future owner, ensuring to verify the distance, location and basic data about the animal. We count on the development of this work, with the help of Android Studio, where the APP was developed in JAVA language, which is applied to the user interface and, from location sensors, managed lost animals and also adoptions.